2008
DOI: 10.1007/s12010-008-8318-9
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, High Expression and Purification of Recombinant Human Intereferon-β-1b in Escherichia coli

Abstract: Sequential evaluation and process control strategy were employed for impurity profile and high recovery with quality of rhIFN-beta-1b expressed in Escherichia coli. The high-level expression was achieved by using codon substitution (AT content of 52.6% at N-terminal region) and optimization of culture conditions. The addition of rifampicin at a concentration of 200 microg/ml has increased the specific product yield of 66 mg optical density(-1) l(-1) (43.5% of total cellular protein). Eighty-three percent of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Besides IL-10, the cytokines Granulocyte Macrophage Colony-Stimulating Factor (GM-CSF), Interleukin-5 (IL-5) and Interfernon-beta (IFN-β) are also described as 3D domain swapping proteins [9] and have been heterologously expressed in several platforms. Upon expression in E. coli the formation of inclusion bodies were described for these four cytokines [25]–[28]. Although formation of inclusion bodies could be indicative of multimerisation, they are a relatively common feature when expressing eukaryotic proteins in E. coli due to aggregation of folding intermediates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides IL-10, the cytokines Granulocyte Macrophage Colony-Stimulating Factor (GM-CSF), Interleukin-5 (IL-5) and Interfernon-beta (IFN-β) are also described as 3D domain swapping proteins [9] and have been heterologously expressed in several platforms. Upon expression in E. coli the formation of inclusion bodies were described for these four cytokines [25]–[28]. Although formation of inclusion bodies could be indicative of multimerisation, they are a relatively common feature when expressing eukaryotic proteins in E. coli due to aggregation of folding intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…Although formation of inclusion bodies could be indicative of multimerisation, they are a relatively common feature when expressing eukaryotic proteins in E. coli due to aggregation of folding intermediates. However, in the case of IFN-β and IL-5, experiments also demonstrated the need for slow removal of denaturing agents to prevent aggregation to reoccur after solubilisation of inclusion bodies [25], [26]. To our knowledge, IL-5 has not been produced in plants before and expression of human IFN-β in lettuce leaves resulted in poor yields [29].…”
Section: Discussionmentioning
confidence: 99%
“…Already has used sodium deoxycholate and Triton X-100 for removing membrane proteases (39). Dasari also showed that the increase in the concentration of Triton X-100 causes IBs to precipitate via increasing buffer viscosity (40). In this research, the best efficiency of IBs recovery was found at a concentration 0.5 M of Triton X-100 (without the use of Sodium DeoxyCholate in the second phase of the washing stage).…”
Section: Discussionmentioning
confidence: 62%
“…Escherichia coli is a well‐known host for the effective expression of nonglycosylated recombinant proteins . However, the high‐level expression of eukaryotic proteins in E. coli often leads to the formation of insoluble protein aggregates in the cytoplasm, referred to as inclusion bodies (IBs) .…”
Section: Introductionmentioning
confidence: 99%
“…Due to its nature, the solubilization of recombinant proteins expressed as IBs—derived from partially folded intermediates, lipids, carbohydrates, DNA, RNA, and other cellular proteins —is a challenging task. Frequently, IBs are treated with denaturing agents along with detergents and reducing agents to achieve high protein solubilization , considering the requirements of their further processing with the simplest execution.…”
Section: Introductionmentioning
confidence: 99%